Предмет: Русский язык,
автор: daniakot2018
(х+2)*(х-1)*(3х-7)≤0 решение и ответ пожалуйста
Ответы
Автор ответа:
0
(х+2)*(х-1)*(3х-7)≤0
х²-х+2х-2 = (х²+х-2)*(3х-7)≤0
3х³-7х²+3х²-7х-6х+14≤0
3х³-4х²-13х+14≤0
х(3х²-4х-13)+14≤0
х+14≤0 3х²-4х-13≤0
х≤-14 Д=(-4)²-4*3*(-13)=16+156=172=2√43
х1=4-2√43/6= 2(2-√43)/6=2-√43/3
x2=4+2√43/6=2(2+√43)/6=2+√43/3
х²-х+2х-2 = (х²+х-2)*(3х-7)≤0
3х³-7х²+3х²-7х-6х+14≤0
3х³-4х²-13х+14≤0
х(3х²-4х-13)+14≤0
х+14≤0 3х²-4х-13≤0
х≤-14 Д=(-4)²-4*3*(-13)=16+156=172=2√43
х1=4-2√43/6= 2(2-√43)/6=2-√43/3
x2=4+2√43/6=2(2+√43)/6=2+√43/3
Похожие вопросы
Предмет: Математика,
автор: zlatikks
Предмет: Математика,
автор: vanacut38
Предмет: Другие предметы,
автор: nekstufin
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: vasasysauiartausyene